Early Innovations in Copper Hydrometallurgy: The Unknown 1866 Whelpley & Storer Process - W. W. Culver (Canadian Institute of Mining, Metallurgy and Petroleum, 2019)
The paper explores the substance, circumstances and significance of the Whelpley and Storer Copper Process. The 1866 Whelpley and Storer patent specified a process combining mechanical and chemical engineering. The process called for a down-drafting shaft furnace with a horizontal flue connected at the bottom of the shaft. Powdered sulphide ore was roasted in the shaft and then sent forward fully oxidized to a bath of sulphuric acid and/or calcium chloride. The “water furnace” was developed in Boston, at a time when the city was home to most Michigan copper mining companies. The process was field-tested at Quebec’s Harvey Hill copper mine. In 1865 James Douglas, Jr. took over management of the Harvey Hill mine with the challenge of saving the family investment. He needed a way to make money from low-grade sulphides. Through his relationship with chemist T. Sterry Hunt, Douglas learned of a possible way ahead using the process developed by Whelpley and Storer. The paper confirms the centrality of publications, meetings, and networking in the advancement of metallurgy. The process is of interest historically, as much as anything, because it is one of the pillars of James Douglas’ distinguished career in copper. INTRODUCTION At the 1866 meeting of the American Association for the Advancement of Science (AAAS) in Buffalo, New York, T. Sterry Hunt (1826–1892) read a paper “On the Metallurgical System of Messrs. Whelpley and Storer.” The paper is part of a chain of events that constitute the foundation of James Douglas’ (1837–1918) success in the copper mining industry. To understand the career of Douglas over the early years of modern copper mining, we must necessarily start with Whelpley and Storer. Going back to Hunt’s paper, he concluded his remarks by asserting that the Whelpley and Storer Process was “capable of such wide and varied application, that it is probably destined to have a very important influence on the industry of the world” (Hunt, 1867a). He reached this conclusion reasoning that the process had overcome a critical metallurgical hurdle (Hunt, 1867a). Hunt, a geo-chemist in modern terms, recalled that the chemist of those years easily separated copper from “sulphuretted” ores by converting it to a soluble salt from which pure metal was precipitated by “an equivalent of iron.” The problem was to “…apply this principle in the working of copper ores on a great scale...” (Hunt, 1867a). Hunt noted that this very problem had “…engaged the attention of many metallurgists, and has given rise to various processes for obtaining copper by the moist way, many of which are nearly or quite perfect in their operation, but are lacking in practicability and cheapness” (Hunt, 1867a). Hunt thought Whelpley and Storer had overcome the low-grade sulphide hurdle with a commercially viable engineering breakthrough. Yet in the history of copper metallurgy, the process is missing. What happened?